MENAFSIRKAN ISRA’ MI’RAJ: INTEGRASI PERSPEKTIF AL-QUR’AN DAN PENDEKATAN SAINS MODERN - Zakka, Umar (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
The Isra' and Mi'raj events are among the greatest miracles of the Prophet Muhammad, which have theological, historical, and rational dimensions. These events are often debated because they are considered to exceed the limits of human reason, particularly in relation to the Prophet's journey in a short time from the Masjid al-Haram to the Masjid al-Aqsa to Sidrat al-Muntaha. This article aims to analyze the Isra' Mi'raj event from the perspective of the Qur'an and examine its correlation with the development of modern science. This study uses a qualitative approach with a literature study method through analysis of verses from the Qur'an, classical and contemporary interpretations, and relevant scientific studies. The results of the study show that the Qur'an affirms the truth of the Isra' Mi'raj event as a form of Allah's power as well as spiritual reinforcement for the Prophet Muhammad. In addition, several concepts of modern science, such as the theory of the relativity of time and space, can be used as a rational approach to understanding the possibility of this event, although they cannot fully explain its metaphysical dimensions. Therefore, Isra' Mi'raj can be understood as a transcendental event that integrates the dimensions of revelation, rationality, and faith in Islam.